Penggunaan Model PBL Berbantuan Media Diorama Untuk Meningkatkan Berpikir Kritis Materi Ekosistem Sekolah Dasar - Adila, Adnin Cahyadi; Hadiwijaya Z, Rizki; Pratama, Febri Fajar (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This study aims to determine the improvement of students' critical thinking skills in the planning and implementation of the Problem-Based Learning (PBL) model assisted by diorama media on the ecosystem material in Grade V at SDN Cibungkul. The research method used is classroom action research (CAR), conducted in two cycles consisting of four stages: planning, implementation, observation, and reflection. The results of this study show that prior to the intervention, the percentage of students demonstrating critical thinking was 23%. In the first cycle, it increased to 59%, and in the second cycle, it reached 86%, which is an increase of 63% from the pre-intervention stage. Therefore, the result of this study is that the average level of students' critical thinking skills reached 83.4. Thus, the use of the Problem-Based Learning (PBL) model assisted by diorama media can improve students' critical thinking skills in learning about ecosystems.